Novel regenerated pervious concrete and preparation method thereof

By optimizing the particle size and ratio of regenerated aggregates, combined with the optimization of water-glue ratio and additives, the complete replacement of regenerated aggregates in regenerated permeable concrete is achieved, and the mechanical properties and permeable properties of concrete are improved, and the problem of insufficient replacement rate of regenerated aggregates in the prior art is solved.

CN119774949APending Publication Date: 2025-04-08GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996849.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The recycled aggregates in existing recycled permeable concrete cannot be fully replaced, resulting in insufficient mechanical properties and difficult to widely use in actual engineering.

Method used

By controlling the particle size and ratio of regenerated aggregates, a new method of preparation of regenerated water-permeable concrete is adopted, including the use of 5 regenerated aggregates of different particle sizes to perform continuous grading, intermittent grading or single-particle grading, combined with the optimization of water-glue ratio, silica fume usage and permeable concrete reinforcement, the complete replacement of regenerated aggregates is achieved.

Benefits of technology

The pressure resistance, flexural resistance and permeability of recycled permeable concrete are achieved, ensuring that various stress parameters of permeable concrete are not lower than the standard value, achieving the goal of recycled aggregates, and at the same time saving natural aggregate resources and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774949A_ABST
    Figure CN119774949A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of recycled pervious concrete, and discloses novel recycled pervious concrete and a preparation method thereof.The novel recycled pervious concrete is prepared from water, cement, silica fume, a pervious concrete reinforcing agent, aggregate and a water reducing agent, the aggregate is recycled aggregate, and the aggregate comprises at least one of the materials with the particle size being 3-5 mm, 5-10 mm, 10-13.2 mm, 13.2-16 mm and 16-20 mm; the method comprises the following steps: firstly, respectively weighing the components with required mass; then adding the aggregate into a stirrer for stirring and mixing, and then adding water for stirring; adding a cementing material into the stirrer, stirring and mixing, adding a mixture of a water reducing agent and water, and stirring and mixing; pouring the uniformly stirred concrete mixture into a pouring disc; pouring into a mold, and preparing and molding by adopting an inserting and tamping molding mode; and finally, flattening the surface of the formed concrete mixture, covering with a preservative film, standing for a certain time, and demolding. The preparation method is adjusted and improved, so that the aggregate can be completely replaced by the recycled aggregate, and meanwhile, various stress parameters of the concrete cannot be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of recycled aggregate permeable concrete, and in particular to a novel recycled permeable concrete and a preparation method of the novel recycled permeable concrete. Background Art

[0002] As an environmentally friendly and sustainable pavement material, permeable concrete has the environmental advantages of controlling rainwater runoff, improving water quality, replenishing groundwater, reducing road tire noise, regulating road temperature and humidity, and alleviating urban heat island effect due to its special internal structure. It has outstanding advantages in solving the problems of urban heat island effect, insufficient groundwater replenishment, vehicle noise pollution, etc. caused by the covering of non-permeable materials such as concrete and asphalt on the surface of the city with the advancement of urbanization.

[0003] With the continuous acceleration of urbanization, the country's infrastructure construction has also developed rapidly. Many buildings will generate a large amount of construction waste during the construction, demolition and maintenance process. Construction waste has gradually become the largest and most concentrated single type of solid waste in my country's cities, causing huge pressure on the urban waste treatment system. The current common methods of urban waste treatment, such as open-air stacking, sanitary landfill and incineration, have great drawbacks, seriously threatening the environment on which human beings depend for survival, affecting the ecological environment, and contrary to my country's green economy concept.

[0004] The existing patent CN115557755A discloses a low-calcium carbon-fixing regenerated permeable concrete, and the patent CN115215616A discloses a rainstorm-resistant and waterlogging-resistant regenerated permeable concrete suitable for heavy-load traffic pavements. Both disclose the mixing of recycled aggregates with natural aggregates, that is, using recycled aggregates to replace part of the natural aggregates to fill the permeable concrete and act as a skeleton. On the basis of ensuring the performance of the permeable concrete, the recycled aggregates are used to replace natural aggregates in the permeable concrete, which can well realize the resource utilization of construction waste.

[0005] However, the replacement rate of recycled aggregate in the prior art has not reached full replacement. Improving the mechanical properties of pervious concrete with recycled aggregate fully replacing natural aggregate is an urgent problem to be solved in the application of recycled pervious concrete in practical engineering. Summary of the invention

[0006] The main purpose of the present invention is to provide a new type of recycled permeable concrete and a preparation method thereof, aiming to solve the technical problem that recycled aggregates in the components of recycled permeable concrete cannot be completely replaced.

[0007] To achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a novel regenerated permeable concrete, wherein the components of the novel regenerated permeable concrete include water, cement, silica fume, a permeable concrete reinforcing agent, aggregate and a water reducing agent, and the method steps of preparing the novel regenerated permeable concrete include:

[0008] (i) Weigh the required mass of cement, water, aggregate, silica fume, permeable concrete enhancer and water reducing agent respectively; the aggregate is recycled aggregate, and the particle size of the recycled aggregate is at least one of the five particle sizes of 3-5mm, 5-10mm, 10-13.2mm, 13.2-16mm and 16-20mm;

[0009] (ii) Add the weighed recycled aggregate into a mixer and stir for a certain period of time, then add water and stir;

[0010] (iii) adding the cement, the silica fume and the permeable concrete reinforcing agent into the mixer, stirring and mixing for a certain period of time, and then adding the mixture of the water reducing agent and water and stirring and mixing;

[0011] (iv) Pour the evenly mixed concrete mixture into the pouring tray;

[0012] (V) Pour the concrete mixture from the pouring tray into the mold and prepare the mold by ramming:

[0013] (VI) The surface of the formed concrete mixture is smoothed, covered with plastic wrap, and demoulded after being left for a certain period of time.

[0014] Optionally, in one embodiment, the ratio of the aggregate is one of continuous grading, discontinuous grading or single-particle grading. The aggregate of the continuous grading is composed of recycled aggregates of five particle sizes, the aggregate of the discontinuous grading is composed of multiple recycled aggregates of five particle sizes with an interval of one particle size, and the aggregate of the single-particle grading is composed of one of the five recycled aggregates.

[0015] Optionally, in one embodiment, in the continuous grading, the recycled aggregate with a particle size of 3-5 mm accounts for 16-25%, the recycled aggregate with a particle size of 5-10 mm accounts for 9-19%, the recycled aggregate with a particle size of 10-13.2 mm accounts for 8-12%, the recycled aggregate with a particle size of 13.2-16 mm accounts for 9-11%, and the recycled aggregate with a particle size of 16-20 mm accounts for 33-58%.

[0016] Optionally, in one embodiment, in the intermittent grading, the aggregate in the intermittent grading is composed of recycled aggregates with three particle sizes of 3-5mm, 10-13.2mm and 16-19mm, the recycled aggregate with a particle size of 3-5mm accounts for 21-30%, the recycled aggregate with a particle size of 10-13.2mm accounts for 11-15%, and the recycled aggregate with a particle size of 16-19mm accounts for 56-68%.

[0017] Alternatively, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 5-10 mm and 13.2-16 mm, the recycled aggregate with a particle size of 5-10 mm accounts for 12-22%, and the recycled aggregate with a particle size of 13.2-16 mm accounts for 78-88%.

[0018] Alternatively, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 3-5 mm and 10-13.2 mm, the recycled aggregate with a particle size of 3-5 mm accounts for 21-30%, and the recycled aggregate with a particle size of 10-13.2 mm accounts for 70-79%.

[0019] Optionally, in one embodiment, the water-cement ratio of the new recycled permeable concrete raw material is 0.26, the slurry volume accounts for 34%, the amount of silica fume used is 6% of the mass of the cement, and the amount of the permeable concrete reinforcer used is 1% of the mass of the cement.

[0020] Optionally, in one embodiment, the cement is ordinary Portland cement, labeled P.O42.5R.

[0021] Optionally, in one embodiment, the silicon dioxide content in the silica ash is higher than 96.2%, and the ignition loss is lower than 3.92%.

[0022] Optionally, in one embodiment, the water reducer is a polycarboxylic acid high performance water reducer, and the net content is higher than 99.8%.

[0023] Optionally, in one embodiment, the new type of regenerated permeable concrete is placed in water for curing for a certain period of time after demoulding, and the curing time is 28 days.

[0024] The second aspect of the present invention provides a novel regenerated permeable concrete, which is prepared by the novel regenerated permeable concrete preparation method provided by the first aspect.

[0025] In the technical solution provided by the present invention, the method for making recycled permeable concrete is improved, and the recycled aggregate can completely replace the natural aggregate by controlling the particle size, proportion, and preparation method of the recycled aggregate. The recycled permeable concrete prepared by the present invention has excellent compressive strength, good flexural strength, and balanced permeability and antifreeze performance. On the basis of ensuring the performance of the recycled permeable concrete, that is, the various stress parameters of the permeable concrete are not lower than the standard values, the full replacement of the recycled aggregate is achieved, which not only solves the problem of building waste and reduces resource waste, but also reduces the use of natural aggregate resources, and saves energy and protects the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] One or more embodiments are exemplarily described by corresponding drawings, which do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and the figures in the drawings do not constitute proportional limitations unless otherwise stated.

[0027] Figure 1 The present invention is a method flow chart of a novel method for preparing regenerated permeable concrete.

[0028] Figure 2 This is a SEM image of the microscopic test of cement paste after compression of the regenerated permeable concrete specimen of the present invention.

[0029] Figure 3 This is a microscopic test SEM image of the interface between the compressed aggregate and cement paste of the recycled permeable concrete specimen of the present invention.

[0030] Figure 4 This is a SEM image of the cement paste and void microscopic test of the regenerated permeable concrete specimen after compression. DETAILED DESCRIPTION

[0031] For the convenience of understanding the present invention, the present invention will be described in more detail below in conjunction with the accompanying drawings and specific embodiments. All technical and scientific terms used in this specification are identical with the meanings commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more related listed items.

[0032] In addition, the technical features involved in different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0033] Please refer to Figure 1The present invention discloses a method for preparing a novel regenerated permeable concrete. The novel regenerated permeable concrete components include water, cement, silica fume, a permeable concrete reinforcing agent, aggregate and a water reducing agent. The cement, silica fume and the permeable concrete reinforcing agent are cementitious materials. The cementitious materials are used to ensure the overall strength of the regenerated permeable concrete. The water reducing agent is used to ensure the fluidity of the regenerated permeable concrete.

[0034] The method steps of the novel regenerated permeable concrete preparation method are as follows:

[0035] Step 1 S1: Weigh set masses of cement, water, aggregate, silica fume, permeable concrete enhancer and water reducer respectively; wherein the aggregate is recycled aggregate, and the particle size of the recycled aggregate is at least one of the five particle sizes of 3-5mm, 5-10mm, 10-13.2mm, 13.2-16mm and 16-20mm, and all recycled aggregate is used to fill the recycled permeable concrete and play a skeleton role.

[0036] The recycled aggregate required by the present invention is obtained by sieving the recycled aggregate recovered from waste concrete, and is sieved into five different particle sizes of initial recycled aggregate, namely 3-5mm, 5-10mm, 10-13.2mm, 13.2-16mm and 16-20mm. Then, the recycled aggregates of different particle sizes are washed and air-dried respectively. After air-dried, the density of the 3-5mm recycled aggregate is 2530kg / m 3 , the density of 5-10mm recycled aggregate is 2585kg / m 3 , the density of 10-13.2mm recycled aggregate is 2585kg / m 3 , the density of 13.2-16mm recycled aggregate is 2630kg / m 3 The density of 16-20mm recycled aggregate is 2642kg / m 3 .

[0037] Step 2 S2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, and then add water and stir for another 30 seconds to make the aggregate evenly distributed in the mixer, so as to facilitate the balanced distribution of recycled aggregates of different particle sizes or recycled aggregates of a single particle size in the concrete.

[0038] Step 3 S3: Add cement, silica fume and permeable concrete reinforcing agent into the mixer and stir for 30 seconds; add water to the water reducer to form a mixed liquid, and finally add the mixed liquid of the water reducer and water into the mixer and stir for 60 seconds.

[0039] After step three is completed, it is generally necessary to use a shovel to load the freshly mixed recycled permeable concrete from the mixer into the slump bucket in accordance with the standard "Standard Test Method for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016), and conduct a slump test to ensure that the slump of the concrete meets the set target.

[0040] Step 4 S4: Pour the evenly mixed concrete mixture into a pouring tray. The pouring tray is used to facilitate the transfer of the mixed concrete slurry.

[0041] Step 5 S5: pour the concrete mixture from the pouring tray into the mold and prepare it by ramming. Commonly used molds include 100*100*100 triple cube molds and 100*100*400 molds. In the ramming method, it is generally divided into three layers of ramming. The first layer is rammed after adding materials, 1 time for each of the 4 corners, 3 times for each side, and 9 times for each inside of the plane. The remaining two layers are rammed in the same way as above.

[0042] Step 6 S6: The surface of the formed concrete mixture is smoothed, covered with plastic wrap, and removed from the mold after being left for 24 hours.

[0043] After step six, the formed new recycled permeable concrete needs to be placed in water for curing for 28 days.

[0044] In one embodiment, the aggregate ratio is one of continuous grading, discontinuous grading or single particle grading. The continuously graded aggregate is composed of recycled aggregates of five particle sizes. The discontinuous graded aggregate is composed of two or three of the five particle sizes with an interval of one particle size. The single particle grading aggregate is composed of one of the five recycled aggregates.

[0045] In one embodiment, in the continuous grading, the recycled aggregate with a particle size of 3-5 mm accounts for 16-25%, the recycled aggregate with a particle size of 5-10 mm accounts for 9-19%, the recycled aggregate with a particle size of 10-13.2 mm accounts for 8-12%, the recycled aggregate with a particle size of 13.2-16 mm accounts for 9-11%, and the recycled aggregate with a particle size of 16-20 mm accounts for 33-58%.

[0046] In one embodiment, in the discontinuous grading, the aggregate in the discontinuous grading is composed of three kinds of recycled aggregates with particle sizes of 3-5mm, 10-13.2mm and 16-19mm, the recycled aggregate with particle size of 3-5mm accounts for 21-30%, the recycled aggregate with particle size of 10-13.2mm accounts for 11-15%, and the recycled aggregate with particle size of 16-19mm accounts for 56-68%.

[0047] In one embodiment, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 5-10 mm and 13.2-16 mm, the recycled aggregate with a particle size of 5-10 mm accounts for 12-22%, and the recycled aggregate with a particle size of 13.2-16 mm accounts for 78-88%.

[0048] In one embodiment, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 3-5 mm and 10-13.2 mm, the recycled aggregate with a particle size of 3-5 mm accounts for 21-30%, and the recycled aggregate with a particle size of 10-13.2 mm accounts for 70-79%.

[0049] In one embodiment, the water-cement ratio of the new recycled permeable concrete raw material is 0.26, the slurry volume accounts for 34%, the amount of silica fume is 6% of the cement mass, and the amount of permeable concrete enhancer and water reducer is 1% of the cement mass. Permeable concrete enhancer is a special chemical additive, and its main function is to participate in the cement hydration reaction to form a high molecular polymer cement hydration body, thereby significantly improving the strength, durability and frost resistance of cement concrete. The principle of this permeable concrete enhancer is to promote the hydration reaction of cement by reacting with the chemical components in cement, and form a hydration product with excellent mechanical properties.

[0050] In one embodiment, the cement is ordinary Portland cement, labeled P.O42.5R.

[0051] In one embodiment, the silicon dioxide content in the silica fume is higher than 96.2%, and the ignition loss is lower than 3.92%.

[0052] In one embodiment, the water reducing agent is a polycarboxylic acid high performance water reducing agent, the net content of which is higher than 99.8% and the water reducing rate is 0.28.

[0053] In one embodiment, the new regenerated permeable concrete is put into water for curing for a certain period of time after demoulding, and the curing time is 28 days. In other embodiments, the curing time can also be adjusted as needed.

[0054] In a specific embodiment, each cubic meter of concrete contains the following raw materials: 500 kg of cement, 140 kg of water, 1300 kg of aggregate, 30 kg of silica fume, 5 kg of permeable concrete reinforcing agent, and 5 kg of water reducing agent.

[0055] Among them, 3-5mm recycled aggregate is 208~1300kg, 5-10mm recycled aggregate is 156~1300kg, 10-13.2mm recycled aggregate is 130~1300kg, 13.2-16mm recycled aggregate is 130~1300kg or 16-20mm recycled aggregate is 585~1300kg.

[0056] Embodiment 1

[0057] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 Among them, 3-5mm recycled aggregate accounts for 16%, 5-10mm recycled aggregate accounts for 14%, 10-13.2mm recycled aggregate accounts for 10%, 13.2-16mm recycled aggregate accounts for 10% and 16-20mm recycled aggregate accounts for 50%; the paste volume accounts for 34% of the total volume of concrete.

[0058] The steps of preparing the new type of recycled permeable concrete are as follows:

[0059] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and five kinds of aggregates with different particle sizes according to the above proportions.

[0060] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0061] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0062] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0063] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0064] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0065] Example 1 is the first group of continuous grading, which is named C-1.

[0066] Embodiment 2

[0067] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 Among them, 3-5mm recycled aggregate accounts for 21%, 5-10mm recycled aggregate accounts for 14%, 10-13.2mm recycled aggregate accounts for 10%, 13.2-16mm recycled aggregate accounts for 10% and 16-20mm recycled aggregate accounts for 45%; the paste volume accounts for 34% of the total volume of concrete.

[0068] The steps of preparing the new type of recycled permeable concrete are as follows:

[0069] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and five kinds of aggregates with different particle sizes according to the above proportions.

[0070] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0071] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0072] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0073] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0074] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0075] Example 2 is the second group of continuous grading, which is named C-2.

[0076] Embodiment 3

[0077] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 Among them, 3-5mm recycled aggregate accounts for 25%, 5-10mm recycled aggregate accounts for 14%, 10-13.2mm recycled aggregate accounts for 10%, 13.2-16mm recycled aggregate accounts for 10% and 16-20mm recycled aggregate accounts for 41%; the paste volume accounts for 34% of the total volume of concrete.

[0078] The steps of preparing the new type of recycled permeable concrete are as follows:

[0079] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and five kinds of aggregates with different particle sizes according to the above proportions.

[0080] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0081] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0082] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0083] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0084] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0085] Example 3 is the third group of continuous grading, which is named C-3.

[0086] Embodiment 4

[0087] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 Among them, 3-5mm recycled aggregate accounts for 21%, 10-13.2mm recycled aggregate accounts for 15% and 16-20mm recycled aggregate accounts for 64%; the paste volume accounts for 34% of the total volume of concrete.

[0088] The steps of preparing the new type of recycled permeable concrete are as follows:

[0089] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and three kinds of aggregates with different particle sizes according to the above proportions.

[0090] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0091] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0092] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0093] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0094] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0095] Example 4 is the first group of discontinuous grading, which is named G-1.

[0096] Embodiment 5

[0097] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , of which 3-5mm recycled aggregate accounts for 25%, 10-13.2mm recycled aggregate accounts for 15% and 16-20mm recycled aggregate accounts for 60%; the paste volume accounts for 34% of the total volume of concrete.

[0098] The steps of preparing the new type of recycled permeable concrete are as follows:

[0099] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and three kinds of aggregates with different particle sizes according to the above proportions.

[0100] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0101] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0102] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0103] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0104] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0105] Example 5 is the second group of discontinuous grading, which is named G-2.

[0106] Embodiment 6

[0107] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , among which 3-5mm recycled aggregate accounts for 30%, 10-13.2mm recycled aggregate accounts for 15% and 16-20mm recycled aggregate accounts for 55%; the paste volume accounts for 34% of the total volume of concrete.

[0108] The steps of preparing the new type of recycled permeable concrete are as follows:

[0109] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and three kinds of aggregates with different particle sizes according to the above proportions.

[0110] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0111] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0112] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0113] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0114] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0115] Example 5 is the third group of discontinuous grading, which is named G-3.

[0116] Embodiment 7

[0117] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 Among them, 5-10mm recycled aggregate accounts for 12%, 13.2-16mm recycled aggregate accounts for 88%; the paste volume accounts for 34% of the total volume of concrete.

[0118] In Example 8

[0119] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , of which 5-10mm recycled aggregate accounts for 17%, 13.2-16mm recycled aggregate accounts for 83%; the paste volume accounts for 34% of the total volume of concrete.

[0120] Embodiment 9

[0121] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , of which 5-10mm recycled aggregate accounts for 22%, 13.2-16mm recycled aggregate accounts for 78%; the paste volume accounts for 34% of the total volume of concrete.

[0122] The preparation processes of Examples 7, 8 and 9 are the same, and the preparation methods are as follows:

[0123] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and aggregates with two particle sizes of 5-10mm and 13.2-16mm according to the proportion.

[0124] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0125] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0126] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0127] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0128] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0129] Example 7 is the fourth group of discontinuous grading, which is named G-4; Example 8 is the fifth group of discontinuous grading, which is named G-5; Example 9 is the sixth group of discontinuous grading, which is named G-6.

[0130] Embodiment 10

[0131] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , of which 3-5mm recycled aggregate accounts for 21%, 10-13.2mm recycled aggregate accounts for 79%; the paste volume accounts for 34% of the total volume of concrete.

[0132] Embodiment 11

[0133] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3, of which 3-5mm recycled aggregate accounts for 25%, 10-13.2mm recycled aggregate accounts for 75%; the paste volume accounts for 34% of the total volume of concrete.

[0134] Embodiment 12

[0135] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%, that is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 , of which 3-5mm recycled aggregate accounts for 30%, 10-13.2mm recycled aggregate accounts for 70%; the paste volume accounts for 34% of the total volume of concrete.

[0136] The preparation process of Example 10 to Example 12 is the same, and the preparation method is as follows:

[0137] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducer and aggregates with two particle sizes of 3-5mm and 10-13.2mm according to the proportion.

[0138] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0139] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0140] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0141] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0142] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0143] Example 10 is the seventh group of discontinuous grading, which is named G-7; Example 11 is the eighth group of discontinuous grading, which is named G-8; Example 12 is the ninth group of discontinuous grading, which is named G-9.

[0144] Embodiment 13

[0145] In this embodiment, the water-cement ratio of the new recycled permeable concrete is 0.26, the amount of silica fume is 6%, and the amount of water reducer and permeable concrete reinforcing agent is 1%. That is, the amount of cement per unit volume of the new recycled permeable concrete is 500kg, water is 140kg, the amount of silica fume is 30kg, the permeable concrete reinforcing agent is 5kg, and the water reducer is 5kg. The amount of aggregate per unit volume is 1300kg / m 3 The aggregate is 3-5mm recycled aggregate accounting for 100%; the paste volume accounts for 34% of the total volume of concrete.

[0146] Embodiment 14

[0147] Different from the thirteenth embodiment, this embodiment only changes the particle size of the aggregate. The aggregate in the fourteenth embodiment is 100% of 5-10 mm recycled aggregate.

[0148] Embodiment 15

[0149] Different from the thirteenth embodiment, this embodiment only changes the particle size of the aggregate. The aggregate in the fifteenth embodiment is 100% of the 10-13.2 mm recycled aggregate.

[0150] Embodiment 16

[0151] Different from the thirteenth embodiment, this embodiment only changes the particle size of the aggregate. The aggregate in the sixteenth embodiment is 13.2-16 mm recycled aggregate accounting for 100%.

[0152] Embodiment 17

[0153] Different from the thirteenth embodiment, this embodiment only changes the particle size of the aggregate. The aggregate in the sixteenth embodiment is 16-20 mm recycled aggregate accounting for 100%.

[0154] The preparation processes of Example 13 to Example 17 are the same, and the preparation methods are as follows:

[0155] Step 1: Weigh cement, silica fume, permeable concrete enhancer, water reducing agent and recycled aggregate of single-grade particle size according to the proportion.

[0156] Step 2: Add the weighed aggregate into a horizontal shaft forced mixer, stir and mix for 30 seconds, then add some water and stir for 30 seconds.

[0157] Step 3: Add cement, silica fume and permeable concrete enhancer to the mixer and stir for 30 seconds; add water to the water reducer to form a water-reducing mixture, and finally add the water-reducing mixture to the mixer and stir for another 60 seconds. Take a sample from the mixer and put it into a slump bucket, and conduct a slump test. If the slump meets the standard, proceed to the next step.

[0158] Step 4: Pour the evenly mixed concrete mixture into the pouring pan.

[0159] Step 5: Pour the concrete mixture from the pouring tray into a 100*100*100 triple cube mold and a 100*100*400 mold, and prepare it by tamping. It is divided into three layers of tamping. The first layer is tamped after adding materials, once at each of the four corners, three times on each side, and nine times inside the plane. The remaining two layers are tamped in the same way as above.

[0160] Step 6: Smooth the surface of the formed concrete mixture, cover it with plastic wrap, and demould it after 24 hours. After demoulding, the formed new recycled permeable concrete specimen needs to be placed in water for 28 days.

[0161] Example 13 is the first group of single particle grading, which is named S-1; Example 14 is the second group of single particle grading, which is named S-2, Example 15 is the third group of single particle grading, which is named S-3, Example 16 is the fourth group of single particle grading, which is named S-4, and Example 17 is the fifth group of single particle grading, which is named S-5.

[0162] The water permeability coefficient is the most intuitive indicator for measuring the water permeability of permeable concrete. The test pieces of Embodiment 1 to Embodiment 17 were tested for the water permeability coefficient. The test results are shown in Table 1:

[0163] Table 1 Test results of water permeability coefficient of new recycled permeable concrete specimens after 28 days of curing

[0164] serial number 28d water permeability (mm / s) C-1 6.68 C-2 5.99 C-3 5.03 G-1 7.58 G-2 7.05 G-3 6.36 G-4 8.32 G-5 8.20 G-6 8.09 G-7 7.95 G-8 7.36 G-9 7.42 S-1 6.03 S-2 7.04 S-3 7.08 S-4 7.42 S-5 7.06

[0165] As shown in Table 1, the water permeability coefficient of the test pieces of the present invention ranges from 5.03 to 8.32 mm / s, and the water permeability coefficients of all test pieces are higher than the values ​​recommended in the ACI standard. The regenerated permeable concrete prepared by the present invention has good permeability.

[0166] Mechanical properties tests were conducted on the specimens of Example 1 to Example 17, and the test results are as follows:

[0167] Compressive strength test

[0168] Table 2 shows the compressive strength test results of the new recycled permeable concrete after 28 days of curing.

[0169] serial number 28d compressive strength (MPa) C-1 9.52 C-2 11.2 C-3 11.32 G-1 9.99 G-2 10.63 G-3 13.18 G-4 12.39 G-5 12.95 G-6 15.7 G-7 6.83 G-8 8.83 G-9 8.53 S-1 7.27 S-2 8.68 S-3 14.72 S-4 11.56 S-5 7.96

[0170] As shown in Table 2, the compressive strength of the test piece of the present invention is in the range of 6.83 to 15.7 MPa. A more uniform aggregate structure is formed inside, which increases the overall compressive strength. This result shows that the new type of recycled permeable concrete can be used in projects such as sidewalks, pedestrian streets, non-motorized vehicle lanes, squares and parking lots. The test piece after the compression test was scanned by electron microscope to obtain the microscopic test SEM images of the cement paste after compression. Figure 2 , SEM image of the interface between aggregate and cement paste Figure 3 SEM images of cement paste and void microstructure test Figure 4 ,refer to Figure 2 After being compressed, the cracks between cement pastes are relatively small. Figure 3 The cracks at the interface between aggregate and cement paste are also relatively small. Figure 4 After being compressed, no obvious cracks were observed between the cement paste and the voids, so it can be clearly seen that the test specimen of the new type of recycled permeable concrete prepared by the present invention has good compressive resistance.

[0171] Flexural strength test

[0172] Table 3 28d curing flexural strength test results of new recycled permeable concrete

[0173] serial number Flexural strength(MPa) serial number Flexural strength(MPa) C-1 2.64 G-7 1.81 C-2 2.73 G-8 2.14 C-3 2.92 G-9 1.87 G-1 2.62 S-1 1.72 G-2 2.98 S-2 2.26 G-3 3.12 S-3 3.43 G-4 3.24 S-4 2.56 G-5 3.91 S-5 2.44 G-6 4.22

[0174] When conducting the flexural test, the specimens are mainly destroyed by shear and tension. In the recycled permeable concrete, the weak surface subjected to shear and tension is the interface between the recycled aggregate and cement. That is, when subjected to load, the cement bonding interface is generally sheared or tensile, forming cracks and causing the specimen to be destroyed. The relationship of the flexural strength of the specimens of the present invention is: discontinuous gradation > continuous gradation > single particle gradation. Among them, the flexural strength of the recycled permeable concrete prepared by the particle size combination of Examples 7, 8 and 9, i.e., 5-10mm and 13.2-16mm is better than that of other particle size combinations as a whole, and the maximum can reach 4.22MP.

[0175] Antifreeze performance test

[0176] According to the national standard GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the test specimen of the present invention was subjected to freeze-thaw cycle test. According to the "Technical Specifications for Permeable Cement Concrete Pavement", within the specified number of cycles, the compressive strength loss rate cannot exceed 25%, and the mass loss rate is not allowed to exceed 5%. Permeable cement concrete needs to reach D25 in hot summer and cold winter areas, and needs to reach D35 in cold areas. Therefore, this test is designed to have 50 freeze-thaw cycles, and the freeze-thaw medium is an alcohol solution. Under the conditions of 25 and 50 freeze-thaw cycles, the tests of Examples 1 to 17 were carried out on the test specimens for compressive strength, quality, and permeability coefficient after freeze-thaw cycles.

[0177] The water permeability coefficients and growth rates of Examples 1 to 17 after multiple freeze-thaw cycles are shown in the following table:

[0178] Table 4 Test results of water permeability coefficient of new recycled permeable concrete specimens after 28 days of curing

[0179]

[0180] According to the comprehensive analysis in Table 4, with the increase of freeze-thaw cycles, the water permeability coefficient of G-7~G-9 increased significantly compared with G-1~G-6, with the maximum increase reaching 31.02%. When the freeze-thaw cycle was 25 times, with the increase of small particle size, the development trend of G-1~G-3 was different from that of G-4~G-6 and G-7~G-9. When the freeze-thaw cycle was 50 times, with the increase of small particle size, the development trend of G-7~G-9 was different from that of G-1~G-3 and G-4~G-6.

[0181] Under the conditions of 25 and 50 freeze-thaw cycles, the quality changes of recycled permeable concrete with different gradations, and the compressive strength test results of Examples 1 to 17 after multiple freeze-thaw cycles are shown in the following table:

[0182] Table 5 Test results of folding and compression ratio of new recycled permeable concrete specimens after 28 days of curing

[0183]

[0184]

[0185] It can be seen from Table 5 that the mass loss rate of the recycled permeable concrete with continuous grading is 1.84% to 3.24% after 25 freeze-thaw cycles, and the mass loss rate is 3.19% to 4.6% after 50 freeze-thaw cycles, and the mass loss rate increases by 0.44-0.73. The mass loss rate of the recycled permeable concrete with discontinuous grading is 1.52% to 3.65% after 25 freeze-thaw cycles, and the mass loss rate is 2.02% to 6.04% after 50 freeze-thaw cycles, and the mass loss rate increases by 0.32-0.88. The mass loss rate of the recycled permeable concrete with single particle grading is 1.2% to 2.95% after 25 freeze-thaw cycles; the mass loss rate is 2.06% to 5.26% after 50 freeze-thaw cycles, but the mass loss rate gradually increases with the increase of particle size, and the mass loss rate increases by 0.51-0.83. Comprehensive analysis of all gradations showed that the mass loss rates of discontinuous gradations G-1 to G-6 showed lower mass loss rates after 25 and 50 freeze-thaw cycles.

[0186] Under the conditions of 25 and 50 freeze-thaw cycles, the compressive strength of recycled permeable concrete with different gradations changes. The specific compressive strength change data are as follows:

[0187] Table 6 Compressive strength and loss rate of 28-day curing specimens of new recycled permeable concrete

[0188]

[0189]

[0190] According to the changes in compressive strength and compressive strength loss rate after freeze-thaw cycles in Tables 5 and 6, for continuous grading, with the increase of small-size aggregate and the decrease of large-size aggregate, after 25 freeze-thaw cycles, the compressive strength loss rate is between 9.35% and 10.07%, and the compressive loss rate gradually increases; after 50 freeze-thaw cycles, the compressive strength loss rate is between 18.30% and 19.33%, showing a trend of first decreasing and then increasing.

[0191] For discontinuous grading G-1~G-3, with the increase of 3-5mm aggregate and the decrease of 16-20mm aggregate, after 25 freeze-thaw cycles, the compressive strength loss rate is between 7.06% and 11.41%; after 50 freeze-thaw cycles, the compressive strength loss rate is between 16.31% and 23.72%, and the compressive strength loss rate shows a trend of gradually decreasing. For discontinuous grading G-4~G-6, with the increase of 5-10mm aggregate and the decrease of 13.2-16mm aggregate, after 25 freeze-thaw cycles, the compressive strength loss rate is between 7.13% and 8.03%, showing a trend of first slowly increasing and then decreasing; after 50 freeze-thaw cycles, the compressive strength loss rate is between 14.46% and 17.92%, and the compressive strength loss rate shows a trend of gradually decreasing. For discontinuous gradings G-7 to G-9, with the increase of 3-5 mm aggregate and the decrease of 10-13.2 mm aggregate, after 25 freeze-thaw cycles, the compressive strength loss rate is between 13.6% and 14.35%, showing a gradually decreasing trend; after 50 freeze-thaw cycles, the compressive strength loss rate is between 28.09% and 30.45%, and its compressive strength loss first decreases and then increases.

[0192] For single-particle grading, with the gradual increase of particle size, after 25 freeze-thaw cycles, the compressive strength loss rate is between 9.51% and 13.76%, and after 50 freeze-thaw cycles, the compressive strength loss rate is between 19.43% and 36.93%, both showing a trend of first decreasing and then increasing.

[0193] In summary, as the freeze-thaw cycle progresses, the compressive strength and mass gradually decrease, while the water permeability coefficient gradually increases; the mass loss rate of the discontinuous gradation G-1 to G-6 shows a low mass loss rate at 25 and 50 freeze-thaw cycles. The aggregate on the surface of the specimen has less spalling and shallow cracks, and the frost resistance is good.

[0194] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Although the present invention has been described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the above embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a new type of regenerated permeable concrete, wherein the components of the new type of regenerated permeable concrete include water, cement, silica fume, a permeable concrete reinforcing agent, aggregate and a water reducing agent, and the method is characterized in that: The method steps of the novel regenerated permeable concrete preparation method include: (i) Weigh the required mass of cement, water, aggregate, silica fume, permeable concrete enhancer and water reducing agent respectively; the aggregate is recycled aggregate, and the particle size of the recycled aggregate is at least one of the five particle sizes of 3-5mm, 5-10mm, 10-13.2mm, 13.2-16mm and 16-20mm; (ii) Add the weighed recycled aggregate into a mixer and stir for a certain period of time, then add water and stir; (iii) adding the cement, the silica fume and the permeable concrete reinforcing agent into the mixer, stirring and mixing for a certain period of time, and then adding the mixture of the water reducing agent and water and stirring and mixing; (iv) Pour the evenly mixed concrete mixture into the pouring tray; (V) pouring the concrete mixture from the pouring tray into the mold and preparing the mold by ramming; (VI) The surface of the formed concrete mixture is smoothed, covered with plastic wrap, and demoulded after being left for a certain period of time.

2. The method for preparing the new type of regenerated permeable concrete according to claim 1, characterized in that: The aggregate ratio is one of continuous grading, discontinuous grading or single-particle grading. The aggregate of the continuous grading is composed of recycled aggregates of five particle sizes. The aggregate of the discontinuous grading is composed of multiple recycled aggregates of five particle sizes with an interval of one particle size. The aggregate of the single-particle grading is composed of one of the five recycled aggregates.

3. The method for preparing the new type of regenerated permeable concrete according to claim 2, characterized in that: In the continuous grading, the proportion of recycled aggregate with a particle size of 3-5 mm is 16-25%, the proportion of recycled aggregate with a particle size of 5-10 mm is 9-19%, the proportion of recycled aggregate with a particle size of 10-13.2 mm is 8-12%, the proportion of recycled aggregate with a particle size of 13.2-16 mm is 9-11%, and the proportion of recycled aggregate with a particle size of 16-20 mm is 33-58%.

4. The method for preparing the new type of regenerated permeable concrete according to claim 2, characterized in that: In the discontinuous grading, the aggregate in the discontinuous grading is composed of recycled aggregates of three particle sizes: 3-5 mm, 10-13.2 mm and 16-19 mm, the recycled aggregates of 3-5 mm particle size account for 21-30%, the recycled aggregates of 10-13.2 mm particle size account for 11-15%, and the recycled aggregates of 16-19 mm particle size account for 56-68%; Alternatively, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 5-10 mm and 13.2-16 mm, the recycled aggregate with a particle size of 5-10 mm accounts for 12-22%, and the recycled aggregate with a particle size of 13.2-16 mm accounts for 78-88%; Alternatively, the aggregate in the discontinuous grading is composed of recycled aggregates with two particle sizes of 3-5 mm and 10-13.2 mm, the recycled aggregate with a particle size of 3-5 mm accounts for 21-30%, and the recycled aggregate with a particle size of 10-13.2 mm accounts for 70-79%.

5. The method for preparing the new type of regenerated permeable concrete according to claim 2, characterized in that: The water-cement ratio of the novel recycled permeable concrete raw material is 0.26, the slurry volume accounts for 34%, the amount of silica fume used is 6% of the mass of the cement, and the amount of the permeable concrete reinforcing agent used is 1% of the mass of the cement.

6. The method for preparing the novel regenerated permeable concrete according to claim 1, characterized in that: The cement is ordinary Portland cement, with the designation P.O42.5R.

7. The method for preparing the novel regenerated permeable concrete according to claim 1, characterized in that: The silicon dioxide content in the silica ash is higher than 96.2%, and the ignition loss is lower than 3.92%.

8. The method for preparing the novel regenerated permeable concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high-performance water reducing agent, and the net content is higher than 99.8%.

9. The method for preparing the novel regenerated permeable concrete according to claim 1, characterized in that: After demoulding, the novel regenerated permeable concrete is placed in water for curing for a certain period of time, and the curing time is 28 days.

10. A new type of recycled permeable concrete, characterized in that: The novel regenerated permeable concrete is prepared by a novel regenerated permeable concrete preparation method according to any one of claims 1 to 9.